The phenomenology of attentional control: a first-person approach to contemplative science and the issue of free will - Terje Sparby; Terje Sparby; Terje Sparby; Dirk Cysarz; Dirk Cysarz; David Hornemann v. Laer; David Hornemann v. Laer; David Hornemann v. Laer; Friedrich Edelhäuser; Friedrich Edelhäuser; Friedrich Edelhäuser; Diethard Tauschel; et al. (Frontiers in Psychology, 2024)
There are two basic aspects of attentional control. The ability to direct attention toward different objects is typically experienced as a fundamental indicator of attentional freedom. One can control what one attends to and directing attention is a relatively simple task. In contrast, sustaining attention on a chosen object proves to be difficult as mind-wandering seems to be inevitable. Does the problem of sustaining attention, mean that we are fundamentally unfree? We discuss this issue in light of an introspective study of directing and sustaining attention, looking specifically into the question of whether it is possible to experience the source of attention, i.e., the subject enacting freedom through attention. The study involved six persons performing different attention tasks over the course of about a month. Common experiences and contrasting reports are presented. This forms the basis for a discussion of the method of introspection and in particular of how to approach conflicting reports.